Feasibility of Treating Irradiated Bone with Intramedullary Delivered Autologous Mesenchymal Stem Cells. (29th August 2011) - Phulpin, Bérengère; Dolivet, Gilles; Marie, Pierre-Yves; Poussier, Sylvain; Huger, Sandrine; Bravetti, Pierre; Graff, Pierre; Merlin, Jean-Louis; Tran, Nguyen
Abstract : Background . We aimed to explore (i) the short-term retention of intramedullary implanted mesenchymal stem cells BMSCs and (ii) their impact on the bone blood flow and metabolism in a rat model of hindlimb irradiation. Methods . Three months after 30 Gy irradiation, fourteen animals were referred into 2 groups: a sham-operated group (n = 6 ) and a treated group (n = 8 ) in which 111 In-labelled BMSCs (2 × 10 6 cells) were injected in irradiated tibias. Bone blood flow and metabolism were assessed by serial T 99 m c -HDP scintigraphy and 1-wk cell retention by recordings of T 99 m c / 111 In activities. Results . The amount of intramedullary implanted BMSCs was of 70% at 2 H, 40% at 48 H, and 38% at 168 H. Bone blood flow and bone metabolism were significantly increased during the first week after cell transplantation, but these effects were found to reduce at 2-mo followup. Conclusion . Short-term cell retention produced concomitant enhancement in irradiated bone blood flow and metabolism.